Α, β‐Unsaturated Gold(I) Carbenes by Tandem Cyclization and 1, 5‐Alkoxy Migration of 1, 6‐Enynes: Mechanisms and Applications. Issue 38 (16th August 2016) - Calleja, Pilar; Pablo, Óscar; Ranieri, Beatrice; Gaydou, Morgane; Pitaval, Anthony; Moreno, María; Raducan, Mihai; Echavarren, Antonio M.
Abstract: 1, 6‐Enynes bearing OR groups at the propargyl position generate α, β‐unsaturated gold(I)‐carbenes/ gold(I) stabilized allyl cations that can be trapped by alkenes to form cyclopropanes or 1, 3‐diketones to give products of α‐alkylation. The best migrating group is p ‐nitrophenyl ether, which leads to the corresponding products without racemization. Thus, an improved formal synthesis of (+)‐schisanwilsonene A has been accomplished. The different competitive reaction pathways have been delineated computationally. Abstract : 1, 6‐Enynes with propargyl OR groups generate α, β‐unsaturated gold(I) carbenes that react with alkenes or 1, 3‐diketones to form cyclopropanes or products of α‐alkylation. p ‐Nitrophenyl ether was found to be the best migrating OR group.